El Gaviotín Negro (Chlidonias niger) y el Burrito Común (Laterallus melanophaius) en Santiago del Estero, Argentina - Quiroga, Oscar B.; Coria, Oscar R.; Gómez, Norberto; Chimino, Graciela; Jorge, Fabián; Rojas, Lilia M.; Llugdar, Jorge E.; Alcalde, Martín (Nuestras Aves, 2015)
Este artículo no cuenta con un resumen.